Variasi Menu, Sisa Makanan, dan Tingkat Kecukupan Energi dan Zat Gizi Santri Putri di Pondok Pesantren - Carissa Cerdasari; Nawang Yudha Prameswari (Politeknik Kesehatan Kemenkes Malang, 2022)
Background: The menu at Islamic boarding school often not varied, as a consequence it can increase food waste and reduce the level of nutritional adequacy in female students. A further impact, female students may become undernutrition and at risk of experiencing health problems such as anemia which has long-lasting effects on adult health. Objective:This study was aimed to describe menu variations, food waste, and the level of nutritional adequacy of female students at the HM Lirboyo Islamic Boarding School, Kediri Regency. Design: This cross-sectional study, involved 11 female students. Respondents assessed menu variations using Likert scale from not at all varied to very varied. Food waste was assessed using the Visual Comstock form, and the level of nutritional adequacy was assessed using food recall 3 x 24h compared to nutritional needs. Results: The menu was assessed by respondents as varied (73 percent) and very varied (27 percent), and for food waste, majority of students (91 percent) left little food. However, 100 percent students have very less energy and nutrients sufficiency. Conclusion: Even though there was little food left, the level of energy and nutrient sufficiency was still deficit. This showed the lack of availability of food served by Islamic boarding school.